Inhibition effect of Na+ and Ca2+ on the bioaccumulation of perfluoroalkyl substances by Daphnia magna in the presence of protein. (6th January 2015) - Xia, Xinghui; Rabearisoa, Andry Harinaina; Dai, Zhineng; Jiang, Xiaoman; Zhao, Pujun; Wang, Haotian
Abstract The authors investigated the individual effects of Ca2+ and Na+ on the bioaccumulation of 6 types of perfluoroalkyl substances (PFASs), including perfluorooctane sulfonate (PFOS), perfluorooctanoic acid (PFOA), perfluorononanoic acid (PFNA), perfluorodecanoic acid (PFDA), perfluoroundecanoic acid (PFUnA), and perfluorododecanoic acid (PFDoA), by Daphnia magna in water with 10 mg L−1 bovine albumin or soy peptone. The bioaccumulation factors of PFASs by D. magna decreased linearly with the increase of Ca2+ and Na+ concentrations. The inhibition effect of Ca2+ was stronger than that of Na+, and the decreasing percentages of the body burden of PFASs in D. magna caused by the increment of 1 mmol L−1 Ca2+ and 1 mmol L−1 Na+ were 41% to approximately 48% and 2% to approximately 5%, respectively, in the presence of soy peptone. The partition coefficients (Kp) of PFASs between protein and water increased with rising Ca2+ and Na+ concentrations. The elevated Kp values led to the reduced concentrations of freely dissolved PFASs. This resulted in a decrease of PFAS bioaccumulation in D. magna, and the body burden of each PFAS was positively correlated with its freely dissolved concentration in water. The present study suggests that cations should be considered in the assessment of bioavailability and risk of PFASs in natural waters containing proteinaceous compounds. Environ Toxicol Chem 2014;9999:1–8. © 2014 SETAC